Soil Moisture Status and Root Contents of Grasses at Different Soil Depths - sinha, B.P.; Chatterjee, B.N. (Journal of Soil and Water Conservation, 2022)
Among higher plants perennial grasses are considered to be able to utilise the maximum amount of natural resources for their growth. The groWth of grasses in India, particularly in Chotanagpur, is seasonal. The growth is maximum during rains and minimum in dry seasons. Interspecific differences (Singh & Chatterjee 1964) are often observed in the dry matter accumulations by difkent grasses in different seasons in dry season the other factors conducive to growth except moisture are available in plenty. The plants interact to this limitation differently. In this paper an account of the work done, to study the amount of moisture and roots present at different depths of soil in different seasons of the year and to get some informations on the utilization of available moisture, have been presented.